1999
DOI: 10.1111/j.1751-0813.1999.tb12920.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of breed of cattle on innate resistance to infection with Anaplasma marginale transmitted by Boophilus microplus

Abstract: Innate resistance of purebred B indicus and crossbred cattle was not significantly different. The results confirm that purebred B indicus and crossbred cattle are sufficiently susceptible to warrant the use of vaccination against Anaplasma infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 14 publications
2
3
0
1
Order By: Relevance
“…Breed susceptibility of anaplasmosis recorded in this study support the report of (Chakraborti 2002;. However others have reported no difference in susceptibility to A. marginale of Bos taurus and Bos indicus crossbred cattle (½ to ¾ Bos indicus) (Otim et al, 1980;Wilson et al, 1980) or Bos indicus and Bos indicus crossbred cattle (Bock et al, 1999). Similarly this report revealed that crossbred cattle were mostly affected (13.26%) with Theileriasis than indigenous cattle (6.86%).…”
Section: Breedsupporting
confidence: 88%
“…Breed susceptibility of anaplasmosis recorded in this study support the report of (Chakraborti 2002;. However others have reported no difference in susceptibility to A. marginale of Bos taurus and Bos indicus crossbred cattle (½ to ¾ Bos indicus) (Otim et al, 1980;Wilson et al, 1980) or Bos indicus and Bos indicus crossbred cattle (Bock et al, 1999). Similarly this report revealed that crossbred cattle were mostly affected (13.26%) with Theileriasis than indigenous cattle (6.86%).…”
Section: Breedsupporting
confidence: 88%
“…Furthermore, epidemiological investigations have suggested that one-host tick species such as R . (subgenus Boophilus ) microplus and D. albipictus were associated with natural transmission of A. marginale (Bock et al, 1999; Ewing et al, 1997), which corroborates at least one report of experimental transmission (Aguirre et al, 1994). Intrastadial or transstadial transmission after interhost transfer are the most likely scenarios in such cases because transovarial transmission is considered unlikely for Anaplasmataceae (Bram and Roby, 1970; Long et al, 2003; Potgeiter, 1981; Stich et al, 1989) and because R. Boophilus microplus has been reported to transfer between bovine hosts (Mason and Norval, 1981).…”
Section: Ticks and The Transmission Of E Canissupporting
confidence: 87%
“…Bos taurus are most susceptible to infection and B. indicus least susceptible. The susceptibility of crossbred animals usually lies somewhere in the middle, but this is not the case for infection with A. marginale, as all breeds and crossbred cattle appear to be equally susceptible to disease caused by this organism (12). There is a continuum in relation to the host' s resistance to disease for other disease-causing organisms (13).…”
Section: Ticks and Tick-borne Diseases In Australiamentioning
confidence: 99%